A 14.7 Ka record of earth surface processes from the arid‐monsoon transitional zone of China. Issue 3 (8th November 2017) - Liu, Jianbao; Chen, Jianhui; Kandasamy, Selvaraj; Chen, Shengqian; Xie, Chengling; Chen, Qiaomei; Lin, Baozhi; Yu, Kaifeng; Xu, Qinghai; Velasco, Victor M.; Chen, Fahu
Abstract: The stability of Earth's critical zone is intimately linked with erosion, weathering and vegetation type and density. Therefore, it affects global biogeochemical processes which in turn affect the global climate by absorbing and reflecting solar radiation, and by altering fluxes of heat, water vapour, carbon dioxide and other trace gases through various feedback mechanisms. However, there is a lack of knowledge about how Earth's critical zone processes have changed over time and their link with past monsoon variability, especially in Asia. The study of lake sediments, which contain a suite of inorganic elemental and isotopic proxies, may facilitate the understanding of the Earth's critical zone processes on millennial timescales. Here we reconstruct the history of erosion–weathering–vegetation interactions since 14.7 ka using geochemical records from a radiocarbon‐dated sediment core from Lake Gonghai in the monsoon‐arid transitional zone of north China. Detrital (Al, Ti, K, Rb) and authigenic (Ca, Sr) elemental records reveal distinct, millennial‐scale, late deglacial‐Holocene erosion and weathering patterns and transitions with the former (latter) elements showing higher (lower) values in warm intervals and vice versa . Chemical Index of Alteration (CIA) molar, a humidity proxy, suggests low humidity during the late deglacial 11.5–14.7 ka, high humidity during the early‐mid Holocene 11.5–3.2 ka, and intermediate humidity during the late Holocene interval since 3.2 ka. The results of cross‐spectral analysis and comparison of our records with other climate reconstructions also suggest a pattern of orbitally‐phased humidity changes in north China. Overall, our results provide evidence for the solar‐forcing of Earth's surface processes in mid‐latitude China under natural climatic conditions. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We reconstructed the history of erosion‐weathering‐vegetation interaction from the lacustrine geochemical data for North China since 14.7 ka. The geochemical results indicated that the low, high and intermediate humidity regimes occurred during the late deglacial 11.5–14.7 ka, early‐mid Holocene 11.5–3.2 ka, and the late Holocene after 3.3 ka, respectively. Such orbitally‐phased humidity changes further suggested that Earth's surface processes in mid‐latitude China are largely controlled by solar forcing‐driven East Asian monsoon under natural climatic conditions.